Response surface methodology-based optimization of hairy roots cultures for in vitro AM production - Priya, PV; Kumutha, K; Subhashini, R; Renuka, R; Sivakumar, T; Kannan, P (Plant Science Today, 2024)
Arbuscular mycorrhizal fungi can do wonders in promoting the crop growth as well maintaining soil health. In vitro root organ culture technology is an exciting avenue for AM biofertilizer production. This study aims to optimize the key influencing factors for enhancing the hairy root production used for in vitro AMF culturing using response surface methodology, a statistical and mathematical tool used for designing optimization studies. Study uses Rhizobium rhizogenes MTCC 2364 for transformation in carrot explant. Factors considered for optimization are concentration of gelling agent (phytagel), carbon source (sucrose) and pH of the Modified Strullu and Romand medium (MSR). Design Expert software uses second order polynomial regression equation for predicting the outcome of each experiment. Totally, 17 experiments were run following Box-Behnken design and average hairy root length and average side branch emergence were taken as response. ANOVA analysis reveals that the concentration of phytagel and sucrose had a strong influence on root length, while the phytagel and pH of the medium had a strong effect on side branch emergence. Overall, taking into account the both responses, concentration of phytagel had a significant impact on hairy root production. The maximum average hairy root length obtained was 1.12 cm and number of side branches emerged were 6.78 per day. Based on these results, the optimal parameters were MSR medium with 3gL-1 phytagel, 11gL-1 sucrose and a pH of 4 for boosting hairy root development. This study is a cost-effective approach and minimizes the time taken for establishing the hairy root technology.